2012
DOI: 10.1115/1.4007823
|View full text |Cite
|
Sign up to set email alerts
|

BTX-A Administration to the Target Muscle Affects Forces of All Muscles Within an Intact Compartment and Epimuscular Myofascial Force Transmission

Abstract: Measurement of forces of mono- and bi-articular muscles of an entire intact muscle compartment can allow for a comprehensive assessment of the effects of Botulinum toxin type A (BTX-A) both at and beyond the injection site, and in conditions close to those in vivo. The goal was to test the hypotheses that BTX-A affects (1) the forces of not only the injected but also the noninjected muscles of the compartment, and (2) epimuscular myofascial force transmission (EMFT). Two groups of Wistar rats were tested: Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 71 publications
5
29
1
2
Order By: Relevance
“…Yet, such data have more potential for improved understanding of effects of BTX‐A on joint mechanics. For example, reduction of active force is variable as a function of muscle length instead of being constant …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, such data have more potential for improved understanding of effects of BTX‐A on joint mechanics. For example, reduction of active force is variable as a function of muscle length instead of being constant …”
mentioning
confidence: 99%
“…showed that the force–length characteristics of both injected soleus and non‐injected plantaris muscles of the cat are affected by the toxin. Exclusive exposure of the tibialis anterior (TA) muscle of the anterior crural compartment of the rat also affects the forces of other muscles within the compartment, including extensor digitorum longus (EDL) and extensor hallucis longus (EHL) . On the other hand, it was also reported that passive forces of muscle exposed to BTX‐A show an increase .…”
mentioning
confidence: 99%
“…To our knowledge, there are no studies to date that have measured intramuscular pressure in a fibrotic muscle, and therefore, we cannot rule out the possibility that increased IMP compensates for the increased resistance to radial expansion. Future work using pathological variation in the ECM (Smith et al 2011; Gao et al 2008; Järvinen et al 2002) or experimental manipulations of ECM stiffness (Yucesoy et al 2012; Turkoglu and Yucesoy 2016) will provide direct tests of the hypotheses generated by our study.…”
Section: Discussionmentioning
confidence: 90%
“…Так, в ряде работ показа-но, что моделирование по методу конечных элементов демонстрирует увеличение длины большинства сарко-меров по сравнению с идентичными саркомерами до начала терапии БТА [41]. Возникновение этого эффекта связывают с взаимодействием мышечных волокон и внеклеточного матрикса [42]. Эффект удли-нения саркомеров способствует повышению потенци-ала для создания активной мышечной силы в непара-лизованных частях мышцы и вызывает уменьшение диапазона длины, в котором мышца снижает свою силу в результате воздействия БТА, особенно сразу после повреждения.…”
Section: Effect On Familial Releationshipsunclassified
“…Flexor hallucis longus 50 (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) Конфликт интересов. Авторы заявляют об отсутствии конфликта интересов.…”
Section: Flexed Toesunclassified